Effects of massive transfusion on oxygen availability - Auler Jr, José Otávio Costa; Bonetti, Eloísa; Hueb, Alexandre Ciappina; Gallas, Filomena Regina Barbosa Gomes; Carmona, Maria José Carvalho (São Paulo Medical Journal, 1998)
OBJECTIVE: To determine oxygen derived parameters, hemodynamic and biochemical laboratory data (2,3 Diphosphoglycerate, lactate and blood gases analysis) in patients after cardiac surgery who received massive blood replacement. DESIGN: Prospective study. SETTING: Heart Institute (Instituto do Coração), Hospital das Clínicas, Faculdade de Medicina, Universidade de São Paulo, Brazil. PARTICIPANTS: Twelve patients after cardiac surgery who received massive transfusion replacement; six of them evolved to a fatal outcome within the three-day postoperative follow-up. MEASUREMENTS AND MAIN RESULTS: The non-survivors group (n=6) presented high lactate levels and low P50 levels, when compared to the survivors group (p<0.05). Both groups presented an increase in oxygen consumption and O2 extraction, and there were no significant differences between them regarding these parameters. The 2,3 DPG levels were slightly reduced in both groups. CONCLUSIONS: This study shows that patients who are massively transfused following cardiovascular surgery present cell oxygenation disturbances probably as a result of O2 transport inadequacy.